Clinical Outcome of Dental Implants Placed with High Insertion Torques (Up to 176 Ncm). (20th May 2011) - Khayat, Philippe G.; Arnal, Hélène M.; Tourbah, Bahige I.; Sennerby, Lars
ABSTRACT Background: Primary stability can be improved by using a tapered implant in a slightly underprepared implant site. This may lead to high compression forces and elevated insertion torques. It has been postulated that disturbance of the local microcirculation may occur, leading to necrosis of the osteocytes and bone resorption. Purpose: Report on the clinical outcome of 42 implants placed with an insertion torque equal or greater than 70 Ncm and evaluate bone levels around these implants. Materials and Methods: This prospective study included 48 patients treated with 66 4.5 mm diameter Tapered Screw‐Vent implants (Zimmer Dental®, Carlsbad, CA, USA). Maximum insertion torque (MIT) was recorded with an electronic torque measuring device (Tohnichi® STC200CN, Hitachi, Tokyo, Japan). Nine implants (control group) presented MIT between 30 and 50 Ncm (mean = 37.1 Ncm) and 42 implants (experimental group) MIT greater than 70 Ncm (mean = 110.6 Ncm, range: 70.8–176 Ncm). Marginal bone levels were recorded at the time of loading and 1 year later for the two groups. Results: After 2–3 months of non‐sumerged healing, all implants were clinically stable. Mean marginal bone resorption was 1.03 mm (SD = 0.44) for the control group (low torque) and 0.72 mm (SD = 0.56) for the experimental group (high torque) at time of loading, and 1.09 (SD = 0.62) and 1.24 mm (SD = 0.75), respectively, after 1 year. There were no significant differences between the two groups for bone stability and implant success rate. Conclusions: The use of high insertion torques (up to 176 Ncm) did not prevent osseointegration. Marginal bone levels in the control and experimental groups were similar both at the time of loading and 1 year later.